2015
DOI: 10.1002/jbmr.2597
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Distribution Width as an Independent Predictor of Long-Term Mortality in Hip Fracture Patients: A Prospective Cohort Study

Abstract: Red blood cell distribution width (RDW) has been found to be a significant prognostic factor of mortality in many cardiovascular diseases. However, a link between RDW at admission with long-term mortality in the hip fracture population has not been well established. Therefore, we sought to evaluate the long-term prognostic value of RDW in a well-defined hip fracture cohort, and to compare the effect of RDW in patients with and without anemia. A prospective cohort study was performed on 1479 hip fracture patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 46 publications
7
43
2
Order By: Relevance
“…Previous studies have recently reported that higher RDW values are related to poor health outcomes for several aging‐related diseases in the elderly population, particularly cardiovascular disease, stroke, and mortality . Few studies have also provided the associations between RDW values and conditions related to musculoskeletal diseases: Higher RDW values were related to poor postoperative outcomes of patients with hip fractures, and people with prevalent morphometric vertebral fractures have higher RDW levels compared with those without such fractures . Together with previous other studies, our findings support that RDW could have clinical meaningful values in the associations with aging‐related conditions, beyond its hematologic usages.…”
Section: Resultssupporting
confidence: 86%
“…Previous studies have recently reported that higher RDW values are related to poor health outcomes for several aging‐related diseases in the elderly population, particularly cardiovascular disease, stroke, and mortality . Few studies have also provided the associations between RDW values and conditions related to musculoskeletal diseases: Higher RDW values were related to poor postoperative outcomes of patients with hip fractures, and people with prevalent morphometric vertebral fractures have higher RDW levels compared with those without such fractures . Together with previous other studies, our findings support that RDW could have clinical meaningful values in the associations with aging‐related conditions, beyond its hematologic usages.…”
Section: Resultssupporting
confidence: 86%
“…The results of our report are substantially supported by recent studies. Previous reports regarding the clinical significance of RDW and grip strength as a surrogate indicator of complications support the claims of the current study [ 4 , 25 , 26 ]. The ability to forecast long-term complication after hip fracture only by RDW have proved effective in one prospective cohort study [ 25 ].…”
Section: Discussionsupporting
confidence: 89%
“…Ten studies provided data on AUC [1420, 37–39, 41], and its value between 0.61 and 0.82. Finally, four studies reported RDW as a categorical variable [13, 17, 22, 42]. We also found the RDW levels were significantly associated with morality with a rank correlation.…”
Section: Resultssupporting
confidence: 56%
“…Among the 32 included studies, 6 studies belonged to the group A [1, 2, 911, 38], 9 studies belonged to the group B [23–25, 2729, 3133], and 17 studies belonged to the group C [1322, 36, 37, 39–43]. As for the effect size, RDW was reported as a continuous variable (per 1% increase) in 16 studies [1, 911, 16, 17, 21–23, 29, 31, 32, 36, 37, 40, 43], as a binary variable in 8 studies [14, 16, 18, 19, 26, 33, 36, 40], and as a categorical variable in 8 studies [2, 13, 17, 22, 25, 27, 29, 42]. The AUC of RDW for mortality prediction was reported in 25 studies.…”
Section: Resultsmentioning
confidence: 99%